The properties of soil stabilize with palm oil clinker (POC) - Wan Muhammad Azfar Wan Azmi (School of Environmental Engineering, University Malaysia Perlis, 2013)
This project was conducted to study the behaviour of soil stabilization using palm oil clinker with the POC-to-soil ratio; 5%, 10%, 15%, and 20%. Soil stabilization is the process of mixing and blending materials into soil to improve certain properties of soil.